Pengaruh Supply Chain Management Terhadap Kinerja Perusahaan Melalui Keunggulan Bersaing - Wulandari; Ria Nelly Sari; Al Azhar L. (Jurnal Ekonomi, 2016)
This research aims to examine the effect of supply chain management on firm performance. In this study, the effect of supply chain management on firm performance is intervened by competitive advantage. The sample of this study is manufacturing firms listed on Bursa Efek Indonesia (BEI) 2014. By using total sampling procedure, 137 firms were selected as a sample and questionnaires were sent to finance,production or marketing manager through the corporate secretary. From 137 set questionnaires were sent, 64 sets were returned and due to missing data/incomplete answers so only 59 sets were analyzed. Data were analyzed by using SPSS program version 20.0. This study found that supply chain management positively affects firm performance. The findings showed that supply chain management positively affects the firm's competitive advantage. Further, the analysis found that competitive advantage positively affects firm performance. Meanwhile, the results proved that ÃŸ value of relationship between the supply chain management and firm performance after entered by competitive advantage was decreased from 0.825 to 0,412. This research concludes that competitive advantage has a role as a partial mediation variable.